Transient particle tracking microrheology of plasma coagulation via the intrinsic pathway - Mao Yating; Tan Mingyang; Kohs Tia C. L.; Sylman Joanna L.; Ngo Anh T. P.; Puy Cristina; McCarty Owen J. T.; Walker Travis W. (Applied Rheology, 2023)
The maintenance of hemostasis to ensure vascular integrity is dependent upon the rapid conversion of zymogen species of the coagulation cascade to their enzymatically active forms. This process culminates in the generation of the serine protease thrombin and polymerization of fibrin to prevent vascular leak at sites of endothelial cell injury or loss of cellular junctions. Thrombin generation can be initiated by the extrinsic pathway of coagulation through exposure of blood to tissue factor at sites of vascular damage, or alternatively by the coagulation factor (F) XII activated by foreign surfaces with negative charges, such as glass, through the contact activation pathway. Here, we used transient particle tracking microrheology to investigate the mechanical properties of fibrin in response to thrombin generation downstream of both coagulation pathways. We found that the structural heterogeneity of fibrin formation was dependent on the reaction kinetics of thrombin generation. Pharmacological inhibition of FXII activity prolonged the time to form fibrin and increased the degree of heterogeneity of fibrin, resulting in fibrin clots with reduced mechanical properties. Taken together, this study demonstrates a dependency of the physical biology of fibrin formation on activation of the contact pathway of coagulation.